Establishment of an Intelligent Wireless EV Charging System Using the Wireless Power Transfer (WPT) Method - Muhtaza, Muhammad Ezam; Zainal, Nurfarina (Evolution in Electrical and Electronic Engineering, 2026)
This paper discusses the development of a smart parking system with inductive power transfer for an electric vehicle (EV) prototype using a circular coil configuration. The system uses an induction-based wireless energy transfer technology to provide continuous charging from the parking location to a vehicle. An ESP32 microcontroller is installed in the parking space as the control centre, handling infrared sensor detection, relay module control, and charging startup. Once a vehicle enters the parking lot and its presence is detected by the infrared sensors, the transmitter coil is switched on along with a cooling fan for thermal control. In an electric vehicle, when another ESP32 acts as the main controller and is connected to a charging module (TP4056), an INA219 DC sensor, and a DC voltage sensor to view input voltage, charging current, battery voltage, and battery %. Parameters are examined in real time through the Blynk platform, and the battery level is displayed on an onboard OLED screen. The study also explores coil alignment in inductive wireless power transfer, where increasing the gap between the transmitter and receiver reduces both the input voltage and the charging efficiency. Experimental findings highlighted that coil spacing greatly affects efficiency, with noticeable differences in charging performance between 0.2 mm and 0.6 mm, and no measurable charging beyond that range. The overall system presents a working IoT-based smart parking and wireless charging solution with integrated monitoring and control features.